개별 학습 지원을 위한 수학 플랫폼 LMS 사례 분석 - 한상지; 김형원; 고호경 (East Asian Mathematical Journal, 2022)
This study compares the functions of the Learning Management Systems (LMS) in three widely used Edu-Tech platforms, that support students’ individualized learning by using the learning characteristics of the students. The rapid advances in artificial intelligence (AI) are broadening their impacts in the education industry, and play a broad role in supporting student learning. In many countries, online classes have become a norm due to the COVID-19 crisis, and the demand for Edu-Tech in classes has increased rapidly. As a result, many countries, including South Korea, are now preparing and implementing various policy measures to adopt Edu-Tech in the class setting. Therefore, in this study, we analyze and compare the structures and characteristics of the three widely used Edu-Tech platforms that support individualized mathematics learning. In particular, we compare the LMSs of the three platforms by considering the elements such as learning design, learning management, learner analysis, learning result analysis, and student management functions. The results of this study give implications in the future directions to take on how to build Edu-Tech platform models that promote students’ individualized mathematics learning in public education.
Keywords: edu-tech; platform; LMS; Mathematics Learning